2013
DOI: 10.3998/jmmh.10381607.0007.103
|View full text |Cite
|
Sign up to set email alerts
|

American Muslim College Students: The Impact of Religiousness and Stigma on Active Coping

Abstract: This study explored the relationships between the variables of stigma, religiousness, active coping, and religious coping in a sample of American Muslim college students. Structural equation modeling of data from 120 American-born Muslim college students indicated that there is a significantly negative relationship between stigma and active coping, and that the relationship between religiousness and active coping is fully mediated by religious coping. Implications of these findings are discussed in terms of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Researchers have stressed that when Muslims misunderstand core Islamic beliefs related to the causes of human problems, this may lead to significant social stigma around pursuing mental health care (Abu-Ras, 2003;Herzig et al, 2013;Soheilian & Inman, 2009;Tanhan, 2019). Fewer researchers reported that perceived social stigma was not a significant barrier for the utilization of mental services particularly when more educated and important individuals within Muslim communities were included in sampling (Ali & Milstein, 2012;Kelly et al, 1996;Khan, 2006;Tanhan & Francisco, 2019;Tanhan & Strack, 2020).…”
Section: Perceived Stigma Toward Seeking Mental Health Services-fourth Factormentioning
confidence: 99%
“…Researchers have stressed that when Muslims misunderstand core Islamic beliefs related to the causes of human problems, this may lead to significant social stigma around pursuing mental health care (Abu-Ras, 2003;Herzig et al, 2013;Soheilian & Inman, 2009;Tanhan, 2019). Fewer researchers reported that perceived social stigma was not a significant barrier for the utilization of mental services particularly when more educated and important individuals within Muslim communities were included in sampling (Ali & Milstein, 2012;Kelly et al, 1996;Khan, 2006;Tanhan & Francisco, 2019;Tanhan & Strack, 2020).…”
Section: Perceived Stigma Toward Seeking Mental Health Services-fourth Factormentioning
confidence: 99%
“…Focusing on the American context, studies demonstrate the salutary effect of religion for both Arab and non-Arab Muslim Americans (e.g., Abu-Raiya, Pargament, and Mahoney 2011; Ai, Peterson, and Huang 2003; Driscoll and Wierzbicki 2012; Goforth etal. 2014; Gulamhussein and Eaton 2015; Herzig etal. 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the literature, the map includes the following 11 main factors: cultural beliefs about mental health issues and their causes and treatments (Al‐krenawi, Graham, Al‐bedah, Kadri, & Sehwail, ; Bagasra, ; Bagasra & Mackinem, ; Thomas, Al‐Qarni, & Furber, ); knowledge about formal mental health services (Abu‐Ras, ; Aloud, ); perceived social stigma toward seeking formal mental health services (Ajzen, ; Ajzen, ; Ali & Milstein, ; Amri & Bemak, ; Ciftci, Jones, & Corrigan, ; Corrigan et al, ; Fischer & Turner, ; Fishbein & Ajzen, ; Herzig, Roysircar, Kosyluk, & Corrigan, ; Khan, ; Soheilian & Inman, ); perceived self‐efficacy or behavioral control (Ajzen, Joyce, Sheikh, & Cote, ; Mackenzie et al, 2004; Romano & Netland, ); institutional (professional) factors (Cook‐Masaud & Wiggins, ; Tanhan, ); use of other informal/traditional resources (Chen, Liu, Tsai, & Chen, ; Padela, Killawi, Forman, DeMonner, & Heisler, ); acculturation (Aprahamian, Kaplan, Windham, Sutter, & Visser, ; Bektas, Demir, & Bowden, ); control variables (e.g., education, sex); attitudes toward seeking formal mental health services (Khan, ; Soheilian & Inman, ; Tummala‐Narra & Claudius, ; Yousef & Deane, ); intention (Kelly, Aridi, & Bakhtiar, ; Tanhan, ); and behavior (use of formal mental health services; Bagasra, ; Tanhan & Strack, ).…”
mentioning
confidence: 99%